1980
DOI: 10.1073/pnas.77.1.462
|View full text |Cite
|
Sign up to set email alerts
|

A cytoplasmic clock with the same period as the division cycle in Xenopus eggs.

Abstract: In most species the cell cycle is arrested in the unfertilized egg. After fertilization the cell cycle is reestablished and a rapid series of cleavages ensues. Preceding the first cleavage in Xenopus the egg undergoes a contraction of its cortex, called the "surface contraction wave," which can be visualized by time-lapse cinematography. This wave of contraction is propagated in a circular manner from the animal pole to the equator. We have found that eggs prevented from cleaving by treatment with antimitotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
165
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(174 citation statements)
references
References 21 publications
(17 reference statements)
4
165
2
Order By: Relevance
“…We investigated the localization of p53 in relation to the cell cycle by microinjection of demembranated sperm nuclei into Xenopus eggs. Microinjection into unfertilized eggs triggers the activation of a cell cycle clock (Hara et al, 1980) and induces micro-injected nuclei to synthesize DNA (Gurdon, 1986). We observed that, when sperm nuclei are injected, all the morphological changes previously described in vitro are reproduced Masui, 1983, 1984), including the entry in S phase (Blow and Laskey, 1986).…”
Section: Xenopus P53 Migrates In the Nuclei During S-phasementioning
confidence: 99%
“…We investigated the localization of p53 in relation to the cell cycle by microinjection of demembranated sperm nuclei into Xenopus eggs. Microinjection into unfertilized eggs triggers the activation of a cell cycle clock (Hara et al, 1980) and induces micro-injected nuclei to synthesize DNA (Gurdon, 1986). We observed that, when sperm nuclei are injected, all the morphological changes previously described in vitro are reproduced Masui, 1983, 1984), including the entry in S phase (Blow and Laskey, 1986).…”
Section: Xenopus P53 Migrates In the Nuclei During S-phasementioning
confidence: 99%
“…Cycles of Cyclin B accumulation and destruction sufficient to drive synchronous cell cycles in the absence of any other protein synthesis occur in both fertilized or activated eggs and in egg extracts (Murray and Kirschner, 1989;Hartley et al, 1996). Although MPF activation cycles in amphibian oocytes and eggs can continue in the absence of nuclei and microtubules (Hara et al, 1980;Shinagawa, 1983;Gerhart et al, 1984;Newport and Kirschner, 1984;Kimelman et al, 1987;Shinagawa, 1992), two lines of evidence have demonstrated that subcellular structure is important for MPF activation, even in cytoplasmic extracts. First, nuclei, centrosomes and microtubules have all been shown to stimulate MPF activation Article published online ahead of print.…”
Section: Introductionmentioning
confidence: 99%
“…Cycles of Cyclin B accumulation and destruction sufficient to drive synchronous cell cycles in the absence of any other protein synthesis occur in both fertilized or activated eggs and in egg extracts (Murray and Kirschner, 1989;Hartley et al, 1996). Although MPF activation cycles in amphibian oocytes and eggs can continue in the absence of nuclei and microtubules (Hara et al, 1980;Shinagawa, 1983;Gerhart et al, 1984;Newport and Kirschner, 1984;Kimelman et al, 1987;Shinagawa, 1992) both in manipulated cells and extracts (Detlaff et al, 1964 and references therein, Gautier, 1987;Iwashita et al, 1998;Pérez-Mongiovi et al, 2000). Second, M-phase entry and exit proceed inhomogeneously within the cell (Masui, 1972;Iwao and Elinson, 1990) and travel as waves from the animal hemisphere, where the nucleus and centrosomes are located, to the vegetal hemisphere (Rankin and Kirschner, 1997;Pérez-Mongiovi et al, 1998).…”
mentioning
confidence: 99%
“…For example, a typical protein with a cytoplasmic diffusion coefficient of D ¼ 500 mm 2 min 21 [25,26] would take hours to travel from the centre to the periphery of a frog egg with radius 600 mm (time t ¼ L 2 /6D ¼ 120 min). By contrast, cell cycle waves traverse similar distances in minutes [1,27] and calcium waves in tens of seconds [7]. This can be understood by assuming an autocatalytic reaction of rate approximately 1 min 21 , resulting in a chemical wave of…”
Section: Chemical Waves: the Basicsmentioning
confidence: 99%
“…In time-lapse images of fertilized eggs made in the 1970s, Hara observed a travelling wave of cortical contraction, visualized by movement of pigment granules. These SCWs occurred just before the first cleavage and proceeded as circular waves from the animal to the vegetal pole [27,28] (figure 2a). SCWs consist of two distinct waves: SCWa was the result of the relaxation of the cortical tension, whereas the succeeding SCWb was a stiffening of the cortex [30].…”
Section: Cell Cycle Progression As a Chemical Wavementioning
confidence: 99%